2017
DOI: 10.1080/14767058.2017.1280018
|View full text |Cite
|
Sign up to set email alerts
|

Maternal outcomes following the initiation of an institutional delayed cord clamping protocol: an observational case–control study

Abstract: An institutional DCC protocol for deliveries <34 weeks was not associated with an identifiable increase in adverse maternal outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 12 publications
3
10
0
Order By: Relevance
“…This finding signifies the risk of bleeding complications in higher-order gestations and this risk might be accentuated by DCC. However, a previous study that monitored maternal outcomes following the initiation of the DCC protocol did not find any increased maternal EBL or PPH associated with DCC [25], consistent with the results of a recent systematic review and meta-analysis of DCC in preterm infants [2]. Since our study was not primarily targeted to assess the effect of DCC on maternal complications, it is possible that the incidence of PPH occurred by chance.…”
Section: Discussionsupporting
confidence: 65%
“…This finding signifies the risk of bleeding complications in higher-order gestations and this risk might be accentuated by DCC. However, a previous study that monitored maternal outcomes following the initiation of the DCC protocol did not find any increased maternal EBL or PPH associated with DCC [25], consistent with the results of a recent systematic review and meta-analysis of DCC in preterm infants [2]. Since our study was not primarily targeted to assess the effect of DCC on maternal complications, it is possible that the incidence of PPH occurred by chance.…”
Section: Discussionsupporting
confidence: 65%
“…Despite limited data, no difference has been found in the rate of postpartum hemorrhage, estimated blood loss, or a prolonged third stage of labor with DCC as compared with ICC. 10,11 Our data on potential adverse maternal outcomes also did not demonstrate a signal for harm with DCC. As DCC becomes a more widely utilized intervention, future studies should be powered to assess maternal outcomes adequately.…”
Section: Commentmentioning
confidence: 51%
“…Our results are consistent with other studies that have assessed implementation of a DCC protocol and found a similar compliance rate of ~70% following initiation of their DCC protocols. 810 Our results on adherence to the protocol suggest that there remains an opportunity for further provider education and quality improvement initiatives regarding compliance with the indications and contraindications to DCC as outlined in the protocol.…”
Section: Commentmentioning
confidence: 88%
“…When we assessed the previous PPH definition of EBL > 1,000 mL for cesarean delivery, our rates are consistent with prior data on PPH in similar studies. 4,5,13 After stratification by mode of delivery, we found an increased risk of PPH in cesarean deliveries postprotocol. This difference may be attributable to a 60-second delay in repair of the bleeding hysterotomy.…”
Section: Discussionmentioning
confidence: 88%
“…Our overall results on PPH are consistent with prior data that have not found an increased risk of PPH with DCC. 1,4,5,13 Using the current definition of PPH of EBL !1,000 mL from the American College of Obstetricians and Gynecologists, we found a high overall rate of PPH in our cesarean delivery subgroup. This is likely because 15% of patients had an EBL equal to 1,000 mL in this subgroup.…”
Section: Discussionmentioning
confidence: 99%